2013
DOI: 10.1097/bot.0b013e31828bacb4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fracture Pattern Stability on Implant Loading in OTA Type 31-A2 Proximal Femur Fractures

Abstract: Type 31-A2 fractures become increasingly unstable with increased medial comminution (or fragment size). SHS-P constructs were more load sharing than SHS-IMN constructs. These findings may help guide the surgeon in choice of implant for a 31-A2 intertrochanteric fracture, leaning toward SHS-IMN for the more unstable fracture patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
1
28
1
1
Order By: Relevance
“…The clinical records including age, gender, injured side, subtypes of A2 fractures [1], the extent of lesser trochanter comminution [11], classification of American Society of Anesthesiologists (ASA), and lateral wall thickness [4] were collected and used in the standard univariate and multivariate analyses. The study flow chart is shown in Fig.…”
Section: Identifying Risk Factors Of Plwfmentioning
confidence: 99%
“…The clinical records including age, gender, injured side, subtypes of A2 fractures [1], the extent of lesser trochanter comminution [11], classification of American Society of Anesthesiologists (ASA), and lateral wall thickness [4] were collected and used in the standard univariate and multivariate analyses. The study flow chart is shown in Fig.…”
Section: Identifying Risk Factors Of Plwfmentioning
confidence: 99%
“…1). 1,11,12,17,18 Selection of proximal femoral plating over CMN in managing fracture patterns amenable to both fixation techniques is largely related to surgeon preference. 2,3 Meta-analysis of the present literature shows no significant differences in clinical outcomes to support CMN over SHS.…”
Section: Indications For Platingmentioning
confidence: 99%
“…In the process of deciding the mode of effective internal fixation, it is imperative to recognize distinct fracture features as well as consider patient bone quality for suitable implant selection and technique. 1 Definitive evidence for utilizing one implant over another is not entirely clear in the literature and recent surgeon trends have inclined toward utilizing CMNs for management. 2,3 However, proximal femoral plating remains a proven and effective option for certain intertrochanteric hip fracture types.…”
mentioning
confidence: 99%
“…В работе M. Marmor с соавторами, посвящен-ной остеосинтезу переломов проксимального отдела бедренной кости, также сделан вывод о том, что утрата медиальной опоры увеличива-ет нестабильность перелома, а имплантаты, обе-спечивающие медиальную поддержку, предпо-чтительнее в использовании при остеосинтезе переломов этой локализации [29]. В 2016 г. N. Briffa с соавторами опубликова-ли результаты биомеханического сравнитель-ного анализа стабильности пластин при осевой нагрузке, расположенных по медиальной и ла-теральной поверхностям дистального отдела бед ренной кости.…”
Section: материал и методыunclassified